Fabrication of ZnO sensor to measure pressure, humidity and sense gases at room temperature by using rapid breakdown anodization method - Khaleel, Reem Saadi; Hashim, Mustafa Shakir (Kuwait Journal of Science, 2020)
Rapid breakdown anodization (RBA) process was used to fabricate ZnO sensor to measure pressure, humidity and sense vapors. This electrochemical process transformed Zn metal to its oxide ZnO as X ray diffraction (XRD) techniques confirmed. RBA formed semispherical ZnO nanoparticles (ZNPs) with sizes ranged from 10 to 20 nm as Scanning electron microscope (SEM) showed. These nanoparticles were deposited on Zn substrates by using electrophoretic deposition (EPD) method. After deposition ZNPs aggregated and formed large continuous bodies. Atomic force microscopy (AFM) images showed the vertical growth of ZNPs and confirmed the existence of porosity between these particles. Sensing parameters of ZnO to pressure were: average sensitivity (0.485 MΩ/bar) and Hysteresis area (0.9 MΩ.bar). Resistance of ZnO (RZnO) varies exponentially with relative humidity RH% and its average humidity sensitivity in the range of (20 to 50 RH%) was 52% and 95% in the range of (50 to 90 % RH). The sensing response to Ammonia, Ethanol and Methanol vapors were recorded with different concentrations. The sensitivity of ZnO senor is greater for Methanol but the it’s selectivity was better for Ammonia.